Cyborg Selves in Battlestar Galactica and Star Trek: The Next Generation: Genre, Hybridity, Identity. - ROSE, MARGARET (Journal of Popular Culture (John Wiley & Sons, Inc.), 2015)
The article examines the science fiction (SF) television series "Battlestar Galactica" which air in 1978-79 and "Star Trek: The Next Generation"which aired from 1987-1994. Topics covered include the contribution of "Battlestar Galactica" to the SF genre, its play with individual and cultural hybrid identities, the scientific racism in the division between human and machine and the difference between the two shows in terms of racial discourses.